2005
DOI: 10.1002/chin.200547001
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Nitrogen—Oxygen Cages N12O2, N14O2, N14O3 and N16O4

Abstract: Molecules consisting entirely of nitrogen have been studied extensively for their potential as high energy density materials (HEDM). However, many such molecules are too unstable to serve as practical energy sources. This has prompted many studies of molecules that are mostly nitrogen but which incorporate heteroatoms into the structure to provide additional stability. In the current study, cages of three-coordinate nitrogen are viewed as candidates for stabilization by insertion of oxygen atoms into the nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Experimentally, it is well-known that pressure favors the formation of nitrogen-rich materials, helping to overcome the energy barrier due to lone pair repulsion, as demonstrated by the employment of high pressure techniques in the synthesis of nitrides. Some unsuccessful attempts to reduce the extreme pressure and temperature conditions for the synthesis of cg-N have been performed by using metallic catalysts or the azide ion as starting material instead of molecular nitrogen . On the other side, many computational studies searching for a convenient approach to reduce the instability of polynitrogen materials have reported the insertion of different heteroatoms (oxygen, , phosphorus, and carbon) into the polynitrogen framework to be efficient in relieving chain or ring strain in the case of several isolated molecular systems with different linear or cage , geometries, increasing both their thermodynamic and kinetic stability. In particular it has been found that for linear N x C 2 molecules the energy release properties vary linearly with the chain length and that the chains exhibit a good resistance to dissociation when terminated on both sides by CN groups .…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it is well-known that pressure favors the formation of nitrogen-rich materials, helping to overcome the energy barrier due to lone pair repulsion, as demonstrated by the employment of high pressure techniques in the synthesis of nitrides. Some unsuccessful attempts to reduce the extreme pressure and temperature conditions for the synthesis of cg-N have been performed by using metallic catalysts or the azide ion as starting material instead of molecular nitrogen . On the other side, many computational studies searching for a convenient approach to reduce the instability of polynitrogen materials have reported the insertion of different heteroatoms (oxygen, , phosphorus, and carbon) into the polynitrogen framework to be efficient in relieving chain or ring strain in the case of several isolated molecular systems with different linear or cage , geometries, increasing both their thermodynamic and kinetic stability. In particular it has been found that for linear N x C 2 molecules the energy release properties vary linearly with the chain length and that the chains exhibit a good resistance to dissociation when terminated on both sides by CN groups .…”
Section: Introductionmentioning
confidence: 99%